State authorities, clergy and parish councils of Russian Orthodox Church in Kalmykia in 1957–1984 - Sergey Belousov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article examines the problem of interaction between state authorities and the governing bodies of the Russian Orthodox Church in Kalmykia in the period of 1957– 1984. The author analyses the state of religious aff airs, the development of relations both between state authorities and Orthodox Church organisations on the one hand, and between the clergy and church authorities on the other. The factors that infl uenced these relations are discussed as well. Another task is to reconstruct the socio-demographic situation of the Orthodox clergy and members of parish councils, as well as to identify and analyse the behavioural strategies of the Orthodox clergy. The article draws on materials of the State Archive of the Russian Federation and the National Archive of Republic of Kalmykia, most of materials being made public for the fi rst time. The study of the religious situation in 1957–1984 has showed that in spite of the strong atheistic propaganda, a certain part of population in Kalmykia steadfastly preserved the Orthodox rites. The main proportion of believers, of regular church-goers and members of local organs of church self-administration was made up by elderly people, mainly women, whereas middle-aged and young people were few. State authorities did not aim to eliminate the existing Orthodox houses of worship, but at the same time suppressed any attempts of believers to set up new churches and parishes. The author of the article comes to the conclusion that the main component of the religious policies was the weakening of the infl uence of the clergy on church-goers and increased supervision of religious life. In these circumstances, the Orthodox clergy in their relations with authorities employed either the strategy of adaptation or confrontation. Confl icts between members of the clergy and church authorities on the one hand and state authorities on the other usually arose on economic grounds and did not have a political character.